First 3D morpho-kinematic model of supernova remnants. The case of VRO 42.05.01 (G166.0+4.3). Issue 4 (14th August 2020) - Derlopa, S; Boumis, P; Chiotellis, A; Steffen, W; Akras, S
ABSTRACT: We present the first three-dimensional (3D) morpho-kinematic (MK) model of a supernova remnant (SNR), using as a case study the Galactic SNR VRO 42.05.01. We employed the astrophysical code SHAPE in which wide field imaging and high-resolution spectroscopic data were utilized, to reconstruct its 3D morphology and kinematics. We found that the remnant consists of three basic distinctive components that we call: a 'shell', a 'wing', and a 'hat'. With respect to their kinematical behaviour, we found that the 'wing'  and the 'shell'  have similar expansion velocities ( V exp  = 115 ± 5 km s −1 ). The 'hat'  presents the lowest expansion velocity of the remnant ( V exp  = 90 ± 20 km s −1 ), while the upper part of the 'shell'  presents the highest velocity with respect to the rest of the remnant ( V exp  = 155 ± 15 km s −1 ). Furthermore, the whole nebula has an inclination of ∼3°–5° with respect to the plane of the sky and a systemic velocity of V sys  = −17 ± 3 km s −1 . We discuss the interpretation of our model results regarding the origin and evolution of the SNR and we suggest that VRO 42.05.01 had an interaction history with an inhomogeneous ambient medium most likely shaped by the mass outflows of its progenitor star.